Jinnah, Linlithgow, and the making of Pakistan : a documentary study - Sareen, Tilak Raj, 1935- (New Delhi : Uppal Pub. House, 2010)
Documentary sources on the making of Pakistan as espoused by Mahomed Ali Jinnah, 1876-1948 through his correspondence with major British officials of the times.
Includes bibliographical references and index.
Keywords: Jinnah, Mahomed Ali, -- 1876-1948 -- Correspondence; Linlithgow, Victor Alexander John Hope, -- Marquess of, -- 1887-1952 -- Correspondence; Pakistan Movement -- Sources; India -- History -- Partition, 1947 -- Sources